Moths (Lepidoptera: Heterocera) collected with light attractant in Serra de Itabaiana National Park, Sergipe, Brazil - Dantas, José Oliveira; Pereira, Arivania Santos; Souto, Leandro Sousa; Marques, Ana Paula Coelho (EntomoBrasilis, 2024)
Lepidoptera includes the butterflies and moths, being considered the second largest order of Insecta, with about 16% of all of the known species in this class. Few lists of Lepidoptera exist for the Northeast of Brazil, a poorly inventoried geographical area. This work had as main objective to accomplish a preliminary study of the moths collected with attractive light at the Parque Nacional Serra de Itabaina, Sergipe, Brazil, verifying the taxonomic diversity and abundance in the study area and analyzing some ecological aspects of the group. A total of 1,450 samples was collected, of which 447 were identified in 19 families. The remaining of the material consisted of 794 microlepidopterous and another 209 not identified specimens. The richness and abundance of lepidopterous did not vary significantly among the dry and rainy seasons (p> 0.05). However, the composition analysis (NMDS) separated the species in two distinct assemblages, but the similarity analysis indicated that this arrangement does not differ significantly (ANOSIM; p = 0.09; R = 0.22), indicating that the nocturnal lepidopterofauna of Serra de Itabaiana stays constant along the year. The time which has a larger number of collected lepidopterous, was from 18:00 to 21:00h. This is a preliminary study, but that serves as reference for other studies with Lepidoptera in Sergipe.